Patients Participating in Nasogastric Tube Insertion through Hypnoanalgesia during High-dose Chemotherapy-induced Aplasia. Issue 1 (2nd January 2023) - Granger, Magali; Anthony, Norah; Lermenier, Cécile; Hue, Delphine; Mear, Jean-Baptiste; Houot, Roch; Moignet-Autrel, Aline; Bernard, Marc; Lamy, Thierry
ABSTRACT: The insertion of a nasogastric (NG) tube is often a difficult experience for both patients and caregivers. This often results in a high failure rate of NG insertion. This pilot study aimed to evaluate the effectiveness, tolerance, and acceptability of hypnoanalgesia to assist self-insertion of an NG tube. Patients undergoing high-dose chemotherapy for autologous or allogeneic hematopoietic stem cell transplantation (HSCT) or acute leukemia and with high risk of aplasia were included in the study. A total of 38 patients were included during 6 consecutive months. They all achieved successful NG tube self-insertion. The NG tube remained in place during hospitalization in 32 cases for an average duration of 15 days. Six patients rejected the NG tube during vomiting but they all voluntarily attempted it again later on and succeeded. The discomfort related to NG-tube insertion was mild. This pilot study suggests that NG tube self-insertion assisted by hypnoanalgesia may be effective, well-accepted, and well-tolerated in patients. These promising findings will need further confirmation.